Barriers to circular economy adoption among adults in the eastern province of Saudi Arabia - Abdalla, Samar M.; Aljeri, Mariam M. (Edelweiss Applied Science and Technology, 2026)
The circular economy (CE) presents a viable strategy for mitigating food waste and extending the lifespan of food products. This study aims to assess the reliability and validity of utilizing ten questions as a tool for measuring barriers to CE adoption and to provide recommendations for policymakers to alleviate these barriers. A sample of 384 Saudi adults, aged 18 and older, from the Eastern Province was chosen to complete the questionnaire. The collected data was then examined using descriptive statistics, Cronbach's Alpha, and Exploratory Factor Analysis (EFA). Cronbach’s Alpha indicates that the questions measuring barriers to CE adoption have good internal consistency. The EFA results also reveal that there is only one component that explains about 63.42% of the total variance in the questions measuring barriers to CE adoption. Therefore, it is important to create and carry out educational and awareness campaigns that focus on practical ways to incorporate CE principles into everyday life. Consequently, the study promotes the need to overcome the barriers hindering CE, accompanied by accepting the questions measuring barriers to CE adoption as a reliable and valid tool for assessing the implementation of CE in Saudi Arabia.